2013
DOI: 10.3389/fpsyg.2013.00593
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of motor and perceptual skills from basketball to darts

Abstract: The quiet eye is a perceptual skill associated with expertise and superior performance; however, little is known about the transfer of quiet eye across domains. We attempted to replicate previous skill-based differences in quiet eye and investigated whether transfer of motor and perceptual skills occurs between similar tasks. Throwing accuracy and quiet eye duration for skilled and less-skilled basketball players were examined in basketball free throw shooting and the transfer task of dart throwing. Skilled ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 44 publications
1
37
0
1
Order By: Relevance
“…The free throw situation in a basketball game has similarities to dart throws in the context of, multiple throws, target acquisition tasks, and repetitive motors skill execution. A study by Rienhoff et al (2013) examined 26 basketball players of different skill levels with no experience in darts and studied the transfer of motor and perceptual skills from basketball to darts. The results of the study showed a positive transfer from basketball to throwing accuracy in darts.…”
mentioning
confidence: 99%
“…The free throw situation in a basketball game has similarities to dart throws in the context of, multiple throws, target acquisition tasks, and repetitive motors skill execution. A study by Rienhoff et al (2013) examined 26 basketball players of different skill levels with no experience in darts and studied the transfer of motor and perceptual skills from basketball to darts. The results of the study showed a positive transfer from basketball to throwing accuracy in darts.…”
mentioning
confidence: 99%
“…As our understanding of perceptual-cognitive expertise advances, it seems clear that perceptual-cognitive phenomena do not operate in isolation. In an effort to determine how QE integrates with other elements of perception, cognition and learning, researchers have begun exploring how QE relates to other concepts, such as focus of attention (Rienhoff, Fischer, Strauss, Baker, & Schorer, 2015), fields of vision (Rienhoff, Fischer, Strauss, Schorer, & Baker, 2012), and transfer of learning (Rienhoff et al, 2013). More work of this nature could be quite revealing regarding how the QE might be best utilized.…”
Section: Integrationmentioning
confidence: 99%
“…It suggests that tasks expressing a similar production, outcome or performance environment may afford greater transference (i.e., a positive transfer of learning) [3,4]. The principle of learning transfer has been examined in and across a range of scientific disciplines, such as educational science [5], health and medical science [6], rehabilitation science [7], and sport science [8]. With a focus on the sport sciences, there has been a large quantity of work examining motor and perceptual learning transfers between sports or performance environments [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Using nMDS, this example aims to delineate the dissimilarity of teams ranked high or low on the ladder at the conclusion of the 2016 NRL premiership season.Methodology: Fifteen team performance indicators were extracted from a commercial source (http://www.nrl.com/stats) for each of the 16 NRL teams following the 2016 season. Teams were apriori classified into quartiles based upon their ladder ranking; these being the top four (1-4), upper middle four(5)(6)(7)(8), lower middle four(9)(10)(11)(12) and bottom four(13)(14)(15)(16). Using the team performance indicators, a dissimilarity matrix was built with the Bray-Curtis measure and plotted in two dimensions.…”
mentioning
confidence: 99%